Adsorption-degradation function integrated recoverable catalyst as well as preparation method and application thereof
CoFe2O4@HMCS catalyst that forms a core-shell structure by coating cobalt ferrite nanoparticles, combined with adsorption and catalytic functions, solves the problems of cobalt ferrite nanoparticles prone to agglomeration and Co ion leakage, and achieves efficient removal of organic pollutants in water bodies and good recycling and stability.
Patent Information
- Application Number
- CN202411528307.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, cobalt ferrite nanoparticles are prone to agglomeration in aqueous solution and Co ions are prone to leak, resulting in short service life of the catalyst, difficulty in recycling, and difficulty in efficiently removing organic pollutants in water bodies.
Magnetic CoFe2O4 nanoparticles were prepared by solvothermal method, and the CoFe2O4@HMCS catalyst formed by a core-shell structure was coated by mesoporous hollow carbon spheres. Combined with adsorption and catalytic functions, the electron transfer pathway and free radical pathway degrade organic pollutants to avoid toxicity Formation of by-products.
The stability and catalytic activity of the catalyst are improved, and the ability to efficiently remove organic pollutants in water is achieved. The catalyst is easy to recover magnetically, has a small amount of use, a wide pH range, and has few metal ions leakage, which has good reusability.
Smart Images

Figure CN119259050A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sewage treatment, and in particular to a recyclable catalyst with integrated adsorption and degradation functions, a preparation method and an application thereof. Background Art
[0002] In recent years, with the continuous in-depth development of relevant research in the field of medicine, antibiotics have played an increasingly important role in human production and life. Levofloxacin hydrochloride (LFX) is a classic fluoroquinolone antibiotic with good oral absorption and broad antibacterial activity. It has been widely used in the treatment of infectious diseases such as respiratory tract, urogenital system, gastrointestinal tract and skin. However, due to the abuse, misuse and incomplete metabolism of LFX, the presence of LFX has been repeatedly found in various aquatic environments such as groundwater, surface water, drinking water, and wastewater effluent. On the one hand, LFX residues will not only affect the diversity of aquatic ecosystem communities, but also lead to the production of drug-resistant bacteria and drug-resistant genes; on the other hand, it will affect the human body's immunity and lead to the occurrence of diseases, such as spontaneous tendon rupture, dyspnea, muscle weakness and deterioration, and other symptoms of myasthenia gravis, thus posing a serious threat to human health. Therefore, it is urgent to develop a technology for the efficient removal of LFX.
[0003] In recent years, peroxymonosulfate (PMS)-based advanced oxidation processes (AOPs) have been widely used in the removal of refractory organic pollutants due to their simplicity, mild reaction conditions, high standard redox potential (2.5-3.1 V vs. NHE), long half-life (30-40 μs) and environmental friendliness.
[0004] In the past few years, hollow mesoporous carbon spheres (HMCS) have been used as heterogeneous catalysts for the activation of PMS. For example, PMS can be effectively activated by adjusting the internal type and size of the carbon spheres, and the catalytic activity can be further improved with the reduction of the cavity size and the formation of long pores. Adsorption technology can simply and effectively enrich pollutants on the surface of the adsorbent, but it can only transfer pollutants from one phase to another and cannot completely convert pollutants into small, harmless molecules. Based on the complementarity of the two, the development of advanced materials with both adsorption and catalytic dual functions combined with PMS-AOPs is a feasible and effective strategy. The adsorption performance of the catalyst can further enhance the degradation ability of pollutants.
[0005] Studies have shown that HMCS is also an excellent adsorbent. Since its mesopores with narrow pore size distribution have stronger capillary forces than macropores and are more suitable than micropores, it is most suitable for treating wastewater. In addition, compared with traditional carbon adsorbents, HMCS can be controlled during the synthesis process to achieve extremely high adjustable porosity, large specific surface area and stable physical properties. Its unique hollow mesoporous structure can accelerate the mass transfer rate and provide channels for adsorbates to reach active adsorption sites, thereby improving the adsorption performance of pollutants in wastewater. However, in the catalytic degradation process, the adsorption effect of HMCS is easily excluded or ignored. HMCS has the problem of difficult recovery in practical applications as an adsorbent and catalyst. Some strategies combining magnetic metal oxides with HMCS have been developed to overcome this limitation. Since cobalt ferrite (CoFe2O4) was first found to have catalytic activity for PMS, CoFe2O4 has become one of the most commonly used catalysts for PMS activation due to its high catalytic efficiency and excellent magnetic properties due to the coupling of Co and Fe. However, pure CoFe2O4 nanoparticles with strong magnetism tend to aggregate in aqueous solution, and Co ion leakage is serious, which affects the service life of the catalyst. Therefore, how to develop a catalyst that can avoid aggregation and ion leaching and can efficiently remove organic pollutants is an urgent problem to be solved. Summary of the invention
[0006] The purpose of the present invention is to provide a recyclable catalyst with integrated adsorption-degradation function, a preparation method and an application thereof, so as to solve the problems of the prior art such as difficulty in recovering adsorbents and catalysts, easy leaching of ions, easy agglomeration of nanoparticles, etc.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a recyclable catalyst with integrated adsorption-degradation functions, comprising the following steps:
[0009] A cobalt source, an iron source, sodium acrylate, anhydrous sodium acetate and a solvent are mixed and subjected to a solvothermal reaction to obtain cobalt ferrite;
[0010] Cobalt ferrite, ammonia water, tetrapropoxysilane, resorcinol, formaldehyde, ethanol and water are mixed for reaction; after the reaction, the product is subjected to a first pyrolysis under a protective atmosphere, then etched with alkaline solution, and then subjected to a second pyrolysis under a protective atmosphere to obtain the recyclable catalyst with integrated adsorption-degradation functions.
[0011] Preferably, in the above method for preparing a recyclable catalyst with integrated adsorption-degradation functions, the mass ratio of the cobalt source, the iron source, sodium acrylate and anhydrous sodium acetate is 0.1-0.5:0.2-0.7:1-2:1-3.
[0012] Preferably, in the above-mentioned method for preparing a recyclable catalyst with integrated adsorption-degradation functions, the temperature of the solvent thermal reaction is 180-200° C.; and the time of the solvent thermal reaction is 8-12 hours.
[0013] Preferably, in the above-mentioned method for preparing a recyclable catalyst with integrated adsorption-degradation function, the dosage ratio of the cobalt ferrite, ammonia water, tetrapropoxysilane, resorcinol and formaldehyde is 0.01-0.1g: 1-10mL: 3-8mL: 0.5-2g: 0.1-2mL.
[0014] Preferably, in the above method for preparing the recyclable catalyst with integrated adsorption-degradation function, the reaction process also includes stirring; the stirring time is 20 to 30 hours.
[0015] Preferably, in the above-mentioned method for preparing a recyclable catalyst with integrated adsorption-degradation functions, the temperature of the first pyrolysis is 800-950° C.; and the time of the first pyrolysis is 1-3 hours.
[0016] Preferably, in the above method for preparing a recyclable catalyst with integrated adsorption-degradation functions, the etching temperature is 70 to 100° C.; and the etching time is 24 to 48 hours.
[0017] Preferably, in the above-mentioned method for preparing a recyclable catalyst with integrated adsorption-degradation functions, the temperature of the second pyrolysis is 850-1000° C.; the time of the second pyrolysis is 1-5 hours.
[0018] The present invention also provides a method for preparing a recyclable catalyst with integrated adsorption and degradation functions, and a recyclable catalyst with integrated adsorption and degradation functions.
[0019] The present invention also provides an application of a recyclable catalyst with integrated adsorption-degradation functions in removing organic pollutants from water bodies.
[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention firstly prepares magnetic CoFe2O4 nanoparticles by solvothermal method, and then coats them with mesoporous hollow carbon spheres to obtain a CoFe2O4@HMCS catalyst with a core-shell structure. The hollow mesoporous structure of the catalyst exposes more active sites, which is beneficial to pollutant enrichment adsorption and PMS activation. The adsorption and catalytic functions are combined to improve the catalytic activity and stability of the catalyst, and the material is no longer limited to being used only as an adsorbent or catalyst. There are large structural defects in the carbon sphere shell of the catalyst, which is beneficial to significantly improve the electron donor / acceptor transfer ability and surface adsorption ability during the catalytic process.
[0022] (2) When the catalyst of the present invention is used to remove organic pollutants from water, in the catalyst + PMS + organic pollutant degradation system, the electron transfer pathway plays a leading role in the reaction, while free radicals (·OH and SO4 - ·) pathway plays a key role in the reaction. Compared with the free radical pathway, the catalyst-mediated direct electron transfer pathway has lower oxidant consumption and can avoid the formation of toxic byproducts. The catalyst-rich channels allow pollutants and PMS molecules to diffuse smoothly from the solution into the pores of the catalyst, thereby promoting mass transfer between the target molecule and the material. The catalyst of the present invention has the advantages of small dosage, easy magnetic recovery, wide pH range, less metal ion leaching, and high stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.
[0024] Figure 1 The SEM and TEM characterization images of CoFe2O4@HMCS of Example 1; wherein (a) is the SEM characterization image; (b) is the TEM characterization image;
[0025] Figure 2 XRD diagram, Raman spectrum diagram, BET curve diagram, and hysteresis loop diagram of CoFe2O4@HMCS of Example 1, CoFe2O4 of Comparative Example 1, and HMCS of Comparative Example 2; wherein, (a) is the XRD diagram of CoFe2O4@HMCS of Example 1, CoFe2O4 of Comparative Example 1, and HMCS of Comparative Example 2; (b) is the Raman spectrum diagram of CoFe2O4@HMCS of Example 1 and HMCS of Comparative Example 2; (c) is the BET curve diagram of CoFe2O4@HMCS of Example 1; (d) is the hysteresis loop diagram of CoFe2O4@HMCS of Example 1, CoFe2O4 of Comparative Example 1, and HMCS of Comparative Example 2;
[0026] Figure 3 is the adsorption kinetic curve of LFX;
[0027] Figure 4 The results of adsorption and degradation performance and adsorption-degradation synergistic performance of CoFe2O4@HMCS of Example 1, CoFe2O4 of Comparative Example 1, and HMCS of Comparative Example 2 are shown; wherein (a) is the adsorption and degradation curve of LFX; (b) is the adsorption-degradation synergistic curve of LFX;
[0028] Figure 5 is the cyclic adsorption-degradation synergy curve of LFX;
[0029] Figure 6 is the adsorption-degradation synergy curve of LFX under different initial pH conditions;
[0030] Figure 7 This is the EPR spectrum of the CoFe2O4@HMCS+PMS system with DMPO spin trap;
[0031] Figure 8 This is the EPR spectrum of the CoFe2O4@HMCS+PMS system with TEMP spin trap;
[0032] Fig. 9 It is the IT curve of CoFe2O4@HMCS+PMS+LFX system;
[0033] Fig.10 FT-IR spectrum and XPS spectrum of CoFe2O4@HMCS before and after the reaction; (a) is the FT-IR spectrum; (b) is the XPS spectrum. DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a recyclable catalyst with integrated adsorption-degradation functions, comprising the following steps:
[0035] A cobalt source, an iron source, sodium acrylate, anhydrous sodium acetate and a solvent are mixed and subjected to a solvothermal reaction to obtain cobalt ferrite;
[0036] Cobalt ferrite, ammonia water, tetrapropoxysilane, resorcinol, formaldehyde, ethanol and water are mixed for reaction; after the reaction, the product is subjected to a first pyrolysis under a protective atmosphere, then etched with alkaline solution, and then subjected to a second pyrolysis under a protective atmosphere to obtain the recyclable catalyst with integrated adsorption-degradation functions.
[0037] In the present invention, the cobalt source is preferably one of cobalt chloride hexahydrate, cobalt nitrate hexahydrate, and cobalt sulfate heptahydrate, more preferably cobalt chloride hexahydrate or cobalt nitrate hexahydrate, and more preferably cobalt chloride hexahydrate.
[0038] In the present invention, the iron source is preferably ferric chloride hexahydrate or ferric nitrate nonahydrate, and more preferably ferric chloride hexahydrate.
[0039] In the present invention, the mass ratio of the cobalt source, the iron source, sodium acrylate and anhydrous sodium acetate is preferably 0.1-0.5:0.2-0.7:1-2:1-3, more preferably 0.12-0.3:0.3-0.5:1.2-1.8:1.3-2, and more preferably 0.15867:0.36067:1.5:1.5.
[0040] In the present invention, the usage ratio of the cobalt source and the solvent is preferably 0.1-0.5 g:10-30 mL, more preferably 0.12-0.3 g:15-20 mL, and more preferably 0.15867 g:20 mL.
[0041] In the present invention, the solvent is preferably a mixture of ethylene glycol and diethylene glycol; the volume ratio of ethylene glycol to diethylene glycol is preferably 1:3.
[0042] In the present invention, the temperature of the solvothermal reaction is preferably 180-200°C, more preferably 190-200°C, and more preferably 200°C; the time of the solvothermal reaction is preferably 8-12h, more preferably 9-11h, and more preferably 10h.
[0043] In the present invention, the solvent thermal reaction further includes cooling, washing and vacuum drying after completion.
[0044] In the present invention, the washing is preferably performed using ethanol and water in sequence.
[0045] In the present invention, the vacuum drying temperature is preferably 80-120°C, more preferably 80-100°C, and more preferably 80°C; the vacuum drying time is preferably 10-15h, more preferably 11-13h, and more preferably 12h.
[0046] In the present invention, the dosage ratio of the cobalt ferrite, ammonia water, tetrapropoxysilane, resorcinol and formaldehyde is preferably 0.01-0.1g:1-10mL:3-8mL:0.5-2g:0.1-2mL, further preferably 0.02-0.05g:2-6mL:4-7mL:0.6-1g:0.5-1mL, and more preferably 0.02g:3mL:5mL:0.6g:0.8mL.
[0047] In the present invention, the usage ratio of the cobalt ferrite, ethanol and water is preferably 0.01-0.1 g: 50-70 mL: 10-30 mL, more preferably 0.02-0.05 g: 55-60 mL: 15-25 mL, and more preferably 0.02 g: 60 mL: 20 mL.
[0048] In the present invention, the specific method of mixing the cobalt ferrite, ammonia water, tetrapropoxysilane, resorcinol, formaldehyde, ethanol and water is preferably: ultrasonically dispersing the cobalt ferrite in a system of ethanol, water, ammonia water and tetrapropoxysilane, stirring for 20 minutes, then adding resorcinol, stirring for 5 minutes and then adding formaldehyde.
[0049] In the present invention, the reaction process further includes stirring; the stirring time is preferably 20 to 30 hours, more preferably 22 to 26 hours, and more preferably 24 hours.
[0050] In the present invention, the reaction further comprises centrifugal separation, washing and drying.
[0051] In the present invention, the washing is preferably performed using water and ethanol in sequence.
[0052] In the present invention, the drying temperature is preferably 60-80°C, more preferably 60-70°C, and more preferably 60°C; the drying time is preferably 12-16h, more preferably 12-15h, and more preferably 12h.
[0053] In the present invention, the temperature of the first pyrolysis is preferably 800-950°C, more preferably 880-920°C, and more preferably 900°C; the time of the first pyrolysis is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h; the heating rate of the first pyrolysis is preferably 1-5°C / min, more preferably 3-5°C / min, and more preferably 5°C / min.
[0054] In the present invention, the protective atmosphere is preferably argon.
[0055] In the present invention, the etching temperature is preferably 70-100° C., more preferably 75-90° C., and more preferably 80° C.; the etching time is preferably 24-48 h, more preferably 36-48 h, and more preferably 48 h.
[0056] In the present invention, the alkali solution is preferably a sodium hydroxide solution; the concentration of the alkali solution is preferably 1 to 5 mol / L, more preferably 3 to 4 mol / L, and more preferably 4 mol / L.
[0057] In the present invention, the temperature of the second pyrolysis is preferably 850-1000°C, more preferably 880-950°C, and more preferably 900°C; the time of the second pyrolysis is preferably 1-5h, more preferably 2-3h, and more preferably 2h; the heating rate of the second pyrolysis is preferably 1-5°C / min, more preferably 3-5°C / min, and more preferably 5°C / min.
[0058] The present invention also provides a method for preparing a recyclable catalyst with integrated adsorption and degradation functions, and a recyclable catalyst with integrated adsorption and degradation functions.
[0059] The present invention also provides an application of a recyclable catalyst with integrated adsorption-degradation functions in removing organic pollutants from water bodies.
[0060] In the present invention, the organic pollutant is preferably levofloxacin hydrochloride (LFX).
[0061] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] Example 1
[0063] This embodiment provides a recyclable catalyst (CoFe2O4@HMCS) with integrated adsorption and degradation functions, and its preparation method comprises the following steps:
[0064] (1) 0.36067 g of FeCl3·6H2O, 0.15867 g of CoCl2·6H2O, 1.5 g of sodium acrylate and 1.5 g of anhydrous sodium acetate were dissolved in a mixture of 5 mL of ethylene glycol and 15 mL of diethylene glycol under magnetic stirring; then, the obtained uniform yellow solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and placed in a preheated oven at 200°C for solvothermal reaction for 10 h; after completion, the mixture was cooled to room temperature, washed with ethanol and water, and then vacuum dried at 80°C for 12 h to obtain CoFe2O4;
[0065] (2) 20 mg of CoFe2O4 was ultrasonically dispersed in a solution containing 60 mL of ethanol, 20 mL of water, 3 mL of NH3·H2O and 5 mL of TPOS. After stirring for 20 min, 0.6 g of resorcinol was added. After stirring for 5 min, 0.8 mL of formaldehyde was added and stirring was continued for 24 h. The precipitate was separated by centrifugation, washed with water and ethanol, and dried at 60 °C for 12 h. The dried powder was heated to 900 °C in an Ar atmosphere at a heating rate of 5 °C / min for 2 h. The pyrolysis product was etched with 4 M NaOH at 80 °C for 48 h. The etched product was centrifuged, washed with water and ethanol, and dried in an oven. Then, it was heated to 900 °C in an Ar atmosphere at a heating rate of 5 °C / min for 2 h to obtain the final product, which was recorded as CoFe2O4@HMCS.
[0066] Comparative Example 1
[0067] This comparative example provides a catalyst CoFe2O4, the preparation method of which refers to step (1) of Example 1, and the CoFe2O4 obtained in step (1) of Example 1 is the catalyst CoFe2O4.
[0068] Comparative Example 2
[0069] This comparative example provides a catalyst HMCS, and its preparation method refers to step (2) of Example 1, except that the step of adding CoFe2O4 in step (2) is removed, and the catalyst HMCS is obtained by following the remaining steps of step (2).
[0070] Characterization of catalysts:
[0071] The SEM and TEM characterizations of CoFe2O4@HMCS in Example 1 are as follows: Figure 1 shown. Figure 1 The SEM image in (a) shows that CoFe2O4@HMCS has good dispersion, the prepared catalyst presents a uniform spherical morphology, and a large number of pores are visible on the surface. Figure 1 The TEM image in (b) clearly shows that the CoFe2O4 nanoparticles are encapsulated in the carbon shell, which can avoid the deactivation and aggregation of the metal catalyst.
[0072] The XRD patterns of CoFe2O4@HMCS of Example 1, CoFe2O4 of Comparative Example 1, and HMCS of Comparative Example 2 are as follows: Figure 2 As shown in (a), CoFe2O4@HMCS has a CoFe alloy phase with high crystallinity (JCPDS Card No.48-1816), and three peaks can be detected at 44.4°, 64.8°, and 82.1°, corresponding to the crystal planes (110), (200), and (211), respectively; while the broad peak is assigned to carbon, indicating the amorphous structure of the carbon sphere.
[0073] The Raman spectra of CoFe2O4@HMCS of Example 1 and HMCS of Comparative Example 2 are as follows: Figure 2 As shown in (b), at 1340cm -1 The D band at 1590cm -1 The G band at is a characteristic peak of carbon, showing surface defects and graphite structure. The intensity ratio of the D band to the G band (I D / I G ) reflects the degree of graphitization of the material. The I D / I G The values of 1.080 and 1.089 are respectively, indicating that there are large structural defects in the carbon sphere shell. Such structural defects are beneficial to significantly improve the electron donor / acceptor transfer ability and surface adsorption capacity during the catalytic process.
[0074] The BET curve of CoFe2O4@HMCS in Example 1 is as follows: Figure 3 (c) shows a type IV isotherm pattern, which reveals the mesoporous structure of the carbon particle surface with an average pore size of 12 nm. These carbon spheres are rich in pores, resulting in a BET specific surface area of about 1071 m 2 / g. The higher specific surface area and mesoporous structure expose more active sites, which are beneficial to pollutant enrichment adsorption and PMS activation. The abundant channels allow LFX and PMS molecules to diffuse smoothly from the solution into the pores of the catalyst, thereby promoting mass transfer between the target molecules and the material.
[0075] The hysteresis loops of CoFe2O4@HMCS of Example 1, CoFe2O4 of Comparative Example 1, and HMCS of Comparative Example 2 are as follows: Figure 2 As shown in (d), the saturation magnetizations of CoFe2O4, HMCS, and CoFe2O4@HMCS are 61.928emu / g, 0.017emu / g, and 8.595emu / g, respectively. These values indicate that CoFe2O4 and CoFe2O4@HMCS are ferromagnetic. The reason for the reduction in the magnetic field intensity of CoFe2O4@HMCS is the coating of HMCS, but it can still be separated from the solution by an external magnet.
[0076] Determination of adsorption performance of catalyst:
[0077] Experimental method: In a 100 mL conical flask, 1 mg of catalyst (CoFe2O4@HMCS in Example 1, CoFe2O4 in Comparative Example 1, and HMCS in Comparative Example 2) was dispersed in a 10 mg / L LFX aqueous solution and ultrasonicated for 1 min; at a given time interval, 1.0 mL of the reaction solution was extracted and filtered through a 0.22 μm filter to remove the catalyst; finally, the concentration of residual LFX in the reaction solution was measured at a wavelength of 289 nm using a UV-visible spectrophotometer. Adsorption kinetics Figure 3 As shown in the figure, in the initial stage (0-10 min), the adsorption capacity of LFX increased rapidly because there were enough active sites in the catalyst to capture LFX, and then reached adsorption equilibrium after another 30 min. The pseudo-second-order kinetic model can better describe the adsorption process, which shows that the adsorption process is mainly chemical adsorption, and physical adsorption and chemical adsorption coexist. The order of adsorption capacity is HMCS (471.76 mg / g)>CoFe2O4@HMCS (404.32 mg / g)>CoFe2O4 (170.68 mg / g). The reason for the decrease in adsorption capacity of CoFe2O4@HMCS compared with HMCS may be that CoFe2O4 will shield a small number of active sites, but it still has significant adsorption performance.
[0078] Pseudo-first-order kinetic model:
[0079] Pseudo-second-order kinetic model:
[0080] Where: q e is the equilibrium adsorption capacity, mg / g; q t is the adsorption amount at time t, mg / g; k1 and k2 are the pseudo-first-order adsorption rate constant and pseudo-second-order adsorption rate constant, respectively, g / (mg·min).
[0081] Determination of adsorption-degradation synergistic performance of catalysts:
[0082] Experimental method for determining the adsorption-degradation synergistic performance: In a 100 mL conical flask, 2 mg of catalyst (CoFe2O4@HMCS in Example 1, CoFe2O4 in Comparative Example 1, and HMCS in Comparative Example 2, respectively) was dispersed in a 10 mg / L LFX aqueous solution, ultrasonicated for 1 min, and then 0.5 mM PMS was added to start the degradation reaction; at a given time interval, 1.0 mL of the reaction solution was extracted and quickly mixed with 100 μL of methanol to quench the reaction; the mixture was then filtered through a 0.22 μm filter to remove the catalyst; finally, the concentration of residual LFX in the reaction solution was determined at a wavelength of 289 nm using a UV-visible spectrophotometer.
[0083] Experimental method for adsorption performance determination and degradation performance determination: In a 100 mL conical flask, 2 mg of catalyst (CoFe2O4@HMCS in Example 1, CoFe2O4 in Comparative Example 1, and HMCS in Comparative Example 2, respectively) was dispersed in a 10 mg / L LFX aqueous solution and ultrasonicated for 1 min to conduct an adsorption experiment; 0.5 mM PMS was added after 60 min of the adsorption experiment to start the degradation experiment; within a given time interval, 1.0 mL of the reaction solution was extracted and quickly mixed with 100 μL of methanol to quench the reaction; the mixture was then filtered through a 0.22 μm filter to remove the catalyst; finally, the concentration of residual LFX in the reaction solution was determined at a wavelength of 289 nm using a UV-visible spectrophotometer.
[0084] like Figure 3 As shown in Figure 2, in the individual adsorption processes, after 60 min, the adsorption capacity of CoFe2O4@HMCS, HMCS, and CoFe2O4 for LFX was negligible. Figure 4 As shown, in Figure 4 In (a), the material adsorption equilibrium was reached after 60 min. At this time, the adsorption removal rates of CoFe2O4@HMCS, HMCS and CoFe2O4 for LFX were 56.73%, 47.82% and 4.90%, respectively. After adding PMS for 60 min, the degradation removal rates of LFX were 89.39%, 84.34% and 55.43%, respectively. Figure 4 As shown in (b), under the synergistic effect of good adsorption and degradation, the removal effect of CoFe2O4@HMCS on LFX can reach 84.05% in the first 20 minutes. Subsequently, the adsorption effect slows down, and the removal of LFX mainly depends on PMS activation. After 60 minutes, the synergistic removal rates of CoFe2O4@HMCS, HMCS and CoFe2O4 on LFX are 93.42%, 82.52% and 72.32%, respectively, while it is difficult to effectively degrade LFX using PMS alone. The cyclic adsorption-degradation synergistic effect of LFX is shown in Figure 5 As shown in the figure, after 3 cycles, the removal rate is still 72.21%, indicating that CoFe2O4@HMCS has good reusability.
[0085] Based on the above experimental method, the effect of different initial pH conditions on the degradation of LFX was investigated. The specific method was as follows: before adding the catalyst, 1M H2SO4 and 1MNaOH were used to adjust the pH environment in the reaction system. The degradation curves of LFX under different initial pH conditions are shown in Figure 2. Figure 6 .Depend on Figure 6It can be seen that CoFe2O4@HMCS has advantages in degrading organic matter under neutral pH, weak acidic and weak alkaline conditions. Considering that the pH value of natural water varies between 5 and 9, CoFe2O4@HMCS is suitable for most practical wastewater treatment processes.
[0086] Study on the mechanism of degradation of LFX by catalyst activated PMS:
[0087] Experimental method: (1) Electron paramagnetic resonance (EPR) test: Weigh 10 mg CoFe2O4@HMCS and put it into 1 g / L PMS solution (100 mL) and mix well; 5 minutes later, take 20 μL of each sample, filter it through a 0.22 μm filter membrane, and mix it with 10 μL 100 mM capture agent (DMPO, TEMP). Then use a capillary to take part of the mixed solution and put it into a sample tube for testing. The EPR image of the CoFe2O4@HMCS+PMS system is shown in the figure below: Figure 7 and Figure 8 As shown. (2) Chronoamperometry (IT) test: The catalyst-modified glassy carbon electrode, solid Ag / AgCl electrode and Pt wire electrode were used as the working electrode, reference electrode and counter electrode, respectively. The catalyst ink composed of CoFe2O4@HMCS (1 mg / mL in water) was coated on the glassy carbon electrode. The electrode was dried at room temperature before analysis. IT curve: With 0.05 mM sodium sulfate as the electrolyte, PMS (50 mM) and LFX (500 mg / L) were added at 100 s and 200 s, respectively. The IT curve of the CoFe2O4@HMCS+PMS system is shown in Fig. 9 As shown. Figure 7 and Figure 8 It can be seen that OH and SO4 are produced during the degradation process. - ·Not exist 1 O2. Fig. 9 It can be seen that the injection of PMS after 100s had a significant effect on the current output, indicating that a strong electron transfer occurred between PMS and the CoFe2O4@HMCS surface, forming a PMS / CoFe2O4@HMCS complex; the subsequent addition of LFX resulted in a significant peak in the current of CoFe2O4@HMCS, indicating that electrons were transferred from LFX to the catalyst-PMS complex.
[0088] FT-IR and XPS images of CoFe2O4@HMCS before and after the reaction are shown in Figure 2. Fig.10 As shown. Fig.10 It can be seen that there is no obvious change in the catalyst components and surface groups before and after the reaction, which indicates that CoFe2O4@HMCS has good stability.
[0089] Example 2
[0090] This embodiment provides a recyclable catalyst with integrated adsorption and degradation functions, and its preparation method comprises the following steps:
[0091] (1) 0.572 g of FeCl3·6H2O, 0.2164 g of CoCl2·6H2O, 1 g of sodium acrylate and 2 g of anhydrous sodium acetate were dissolved in a mixture of 5 mL of ethylene glycol and 15 mL of diethylene glycol under magnetic stirring; then, the obtained uniform yellow solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and placed in a preheated oven at 180°C for solvothermal reaction for 8 h; after completion, the solution was cooled to room temperature, washed with ethanol and water, and then vacuum dried at 120°C for 10 h to obtain CoFe2O4;
[0092] (2) 40 mg of CoFe2O4 was ultrasonically dispersed in a solution containing 50 mL of ethanol, 20 mL of water, 5 mL of NH3·H2O and 3 mL of TPOS. After stirring for 20 min, 0.8 g of resorcinol was added. After stirring for 5 min, 0.5 mL of formaldehyde was added and stirring was continued for 25 h. The precipitate was separated by centrifugation, washed with water and ethanol, and dried at 60 °C for 12 h. The dried powder was heated to 880 °C in an Ar atmosphere at a heating rate of 3 °C / min for 1.5 h. The pyrolysis product was etched with 3 M NaOH at 90 °C for 24 h. The etched product was centrifuged, washed with water and ethanol, and dried in an oven. Then, it was heated to 880 °C in an Ar atmosphere at a heating rate of 3 °C / min for 2 h to obtain the final product.
[0093] Example 3
[0094] This embodiment provides a recyclable catalyst with integrated adsorption and degradation functions, and its preparation method comprises the following steps:
[0095] (1) 0.6815 g of FeCl3·6H2O, 0.3089 g of CoCl2·6H2O, 2 g of sodium acrylate and 3 g of anhydrous sodium acetate were dissolved in a mixture of 6 mL of ethylene glycol and 18 mL of diethylene glycol under magnetic stirring; then, the obtained uniform yellow solution was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and placed in a preheated oven at 190°C for solvothermal reaction for 12 h; after completion, the mixture was cooled to room temperature, washed with ethanol and water, and then vacuum dried at 100°C for 14 h to obtain CoFe2O4;
[0096] (2) 70 mg of CoFe2O4 was ultrasonically dispersed in a solution containing 70 mL of ethanol, 30 mL of water, 8 mL of NH3·H2O and 8 mL of TPOS. After stirring for 20 min, 1 g of resorcinol was added. After stirring for 5 min, 2 mL of formaldehyde was added and stirring was continued for 30 h. The precipitate was separated by centrifugation, washed with water and ethanol, and dried at 80 °C for 16 h. The dried powder was heated to 950 °C in an Ar atmosphere at a heating rate of 5 °C / min for 1 h. The pyrolysis product was etched with 5 M NaOH at 100 °C for 36 h. The etched product was centrifuged, washed with water and ethanol, and dried in an oven. Then, it was heated to 850 °C in an Ar atmosphere at a heating rate of 5 °C / min for 3 h to obtain the final product.
[0097] In summary, the present invention prepares core-shell hollow mesoporous carbon spheres encapsulating CoFe2O4 nanoparticles for activating PMS to degrade LFX. Due to the significant adsorption capacity, LFX can be effectively enriched, and free radicals and non-free radical oxidation act together on PMS activation to complete the degradation of LFX. The catalyst can be effectively recovered and reused by magnetic separation, with low dosage, wide pH range, and high stability.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a recyclable catalyst with integrated adsorption and degradation functions, characterized in that: The following steps are involved: A cobalt source, an iron source, sodium acrylate, anhydrous sodium acetate and a solvent are mixed and subjected to a solvothermal reaction to obtain cobalt ferrite; Cobalt ferrite, ammonia water, tetrapropoxysilane, resorcinol, formaldehyde, ethanol and water are mixed for reaction; after the reaction, the product is subjected to a first pyrolysis under a protective atmosphere, then etched with alkaline solution, and then subjected to a second pyrolysis under a protective atmosphere to obtain the recyclable catalyst with integrated adsorption-degradation functions.
2. The method for preparing a recyclable catalyst with integrated adsorption and degradation functions according to claim 1, characterized in that: The mass ratio of the cobalt source, the iron source, the sodium acrylate and the anhydrous sodium acetate is 0.1-0.5:0.2-0.7:1-2:1-3.
3. The method for preparing a recyclable catalyst with integrated adsorption and degradation functions according to claim 2, characterized in that: The temperature of the solvent thermal reaction is 180-200° C.; the time of the solvent thermal reaction is 8-12 hours.
4. The method for preparing a recyclable catalyst with integrated adsorption and degradation functions according to claim 2, characterized in that: The dosage ratio of the cobalt ferrite, ammonia water, tetrapropoxysilane, resorcinol and formaldehyde is 0.01-0.1 g: 1-10 mL: 3-8 mL: 0.5-2 g: 0.1-2 mL.
5. The method for preparing a recyclable catalyst with integrated adsorption and degradation functions according to claim 2 or 4, characterized in that: The reaction process also includes stirring; the stirring time is 20 to 30 hours.
6. The method for preparing a recyclable catalyst with integrated adsorption and degradation functions according to claim 3, characterized in that: The temperature of the first pyrolysis is 800-950° C.; the time of the first pyrolysis is 1-3 hours.
7. The method for preparing a recyclable catalyst with integrated adsorption and degradation functions according to claim 5, characterized in that: The etching temperature is 70-100° C.; the etching time is 24-48 hours.
8. The method for preparing a recyclable catalyst with integrated adsorption and degradation functions according to claim 2 or 6, characterized in that: The temperature of the second pyrolysis is 850-1000° C.; the time of the second pyrolysis is 1-5 hours.
9. A recyclable catalyst with integrated adsorption and degradation functions obtained by the preparation method of a recyclable catalyst with integrated adsorption and degradation functions as claimed in any one of claims 1 to 8.
10. Use of the recyclable catalyst with integrated adsorption and degradation functions as claimed in claim 9 in removing organic pollutants from water.